Ethnic Minorities’ Impression Management in the Interview: Helping or Hindering? - Derous, Eva (Frontiers in Psychology, 2017)
Cross-cultural impression management (IM) has not been considered much, which is remarkable given the fast rate at which the labor market is becoming multicultural. This study investigated whether ethnic minorities and majorities differed in their preference for IM-tactics and how this affected ethnic minorities’ interview outcomes. A preliminary study (focus groups/survey) showed that ethnic minorities (i.e., Arab/Moroccans) preferred ‘entitlements’ whereas majorities (i.e., Flemish/Belgians) preferred ‘opinion conformity’ as IM-tactics. An experimental follow-up study among 163 ethnic majority raters showed no main effect of IM-tactics on interview ratings. Ethnic minorities’ use of IM-tactics only affected interview ratings if rater characteristics were considered. Specifically, interview ratings were higher when ethnic minorities used opinion conformity (i.e., majority-preferred IM-tactic) and lower when minorities used entitlements (i.e., minority-preferred IM-tactic) if recruiters were high in social dominance orientation, and when they felt more experienced/proficient with interviewing. IM-tactics are a human capital factor that might help applicants to increase their job chances on the labor market. It is concluded that ethnic minority applicants’ preferences for certain IM-tactics might lead to bias even in structured interview settings, but that this depends on ethnic majority recruiters’ interview experience and ingroup/outgroup attitudes. Implications for research and practice are discussed.